Singapore’s public housing affordability in terms of income and educational level - Budiman Mohamed Salleh (2011)
Housing is a fundamental issue especially for a small nation like Singapore which utilizes the housing policy as a device that contributes to nation-building. This is evident as it plays a significant role in the economic, social and political development of the country. Housing is imperative to a family nucleus, thus, it is important to examine its affordability to citizens. Our paper analyzes the affordability of public housing in Singapore in terms of income and educational level. This is so as to assist buyers in making informed decisions when purchasing a house, allowing them to exercise financial prudence. In our study, prices of Build-To-Order and resale flats that are built by the Housing & Development Board (HDB) are considered. This report introduces a two-tiered general affordability formula which comprehensively compares the various elements to derive households‟ purchasing ability of flats. Upon conclusion, our study yields results that portray a positive outlook on the general affordability of HDB flats. The findings presented in this report concede that households should steer towards playing an active role in improving their financial situation and boosting their purchasing ability of houses.